2015
DOI: 10.1037/xlm0000146
|View full text |Cite
|
Sign up to set email alerts
|

Learned states of preparatory attentional control.

Abstract: Individuals regularly experience fluctuations in the ability to perform cognitive operations. Although previous research has focused on predicting cognitive flexibility from persistent individual traits as well as from spontaneous fluctuations in neural activity, the role of learning in shaping preparatory attentional control remains poorly understood. Across three experiments, we manipulated the statistical regularities of an attentional orienting paradigm to examine whether individuals modulated attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 82 publications
4
29
0
Order By: Relevance
“…One line of work (e.g., Brady & Oliva, 2008;Kidd, Piantadosi, & Aslin, 2012;Turk-Browne et al, 2005), studied adaptation to the regularity formed by their order (e.g., stimulus 'B' always follows stimulus 'A') and not by interval duration (e.g., 'B' reappears after a predictable interval, yet can be followed by either 'A' or 'C'). Other studies have shown that regular intervals can be implicitly learned: infants (Lewkowicz, 2003) and adults van Rijn, 2017, Olson andChun, 2001, Experiment 1a and b) can implicitly detect rhythmic interval patterns; temporal regularities influence the learning of language (Hay & Saffran, 2012) and artificial pitch grammar (Selchenkova, Jones, & Tillmann, 2014); temporal structure in a rapid serial visual presentation task can bias the probability of shifting the focus of attention (Sali, Anderson, & Yantis, 2015); and temporal information can be integrated in the learning of rhythmic perceptual-motor action sequences (Gobel, Sanchez, & Reber, 2011;O'Reilly, McCarthy, Capizzi, & Nobre, 2008;Schultz, Stevens, Keller, & Tillmann, 2013;Shin & Ivry, 2002). However, it is unclear whether implicit knowledge about regular IMPLICIT LEARNING OF TEMPORAL BEHAVIOR 5 intervals is used to anticipate when to act.…”
Section: Implicit Learning Of Temporal Behavior 3 Implicit Learning Omentioning
confidence: 97%
“…One line of work (e.g., Brady & Oliva, 2008;Kidd, Piantadosi, & Aslin, 2012;Turk-Browne et al, 2005), studied adaptation to the regularity formed by their order (e.g., stimulus 'B' always follows stimulus 'A') and not by interval duration (e.g., 'B' reappears after a predictable interval, yet can be followed by either 'A' or 'C'). Other studies have shown that regular intervals can be implicitly learned: infants (Lewkowicz, 2003) and adults van Rijn, 2017, Olson andChun, 2001, Experiment 1a and b) can implicitly detect rhythmic interval patterns; temporal regularities influence the learning of language (Hay & Saffran, 2012) and artificial pitch grammar (Selchenkova, Jones, & Tillmann, 2014); temporal structure in a rapid serial visual presentation task can bias the probability of shifting the focus of attention (Sali, Anderson, & Yantis, 2015); and temporal information can be integrated in the learning of rhythmic perceptual-motor action sequences (Gobel, Sanchez, & Reber, 2011;O'Reilly, McCarthy, Capizzi, & Nobre, 2008;Schultz, Stevens, Keller, & Tillmann, 2013;Shin & Ivry, 2002). However, it is unclear whether implicit knowledge about regular IMPLICIT LEARNING OF TEMPORAL BEHAVIOR 5 intervals is used to anticipate when to act.…”
Section: Implicit Learning Of Temporal Behavior 3 Implicit Learning Omentioning
confidence: 97%
“…The proposed framework posits a specific role for subcortical reward signals in the shaping of attentional priority. In this regard, value‐driven attention might differ from other influences of selection history on attention, such as intertrial priming, statistical regularities, and status as a former target (under conditions without explicit reward) . However, to the extent that successful identification of a target generates an internal reward signal, similar learning principles might apply in these circumstances.…”
Section: Some Limitations and Outstanding Issuesmentioning
confidence: 99%
“…Importantly, recent studies have extended these findings of “context-control learning” to the case of cognitive flexibility. For example, it has been shown that switch costs can be reduced for stimuli that are presented at a screen location associated with a higher likelihood of task switches (relative to repetitions), even when people are unaware of this contingency (Crump & Logan, 2010; for a similar observation in attention shifting, see Sali, Anderson, & Yantis, 2015). In a similar vein, Farooqui and Manly (2015) demonstrated that subliminally presented (i.e., not consciously perceived) cues signaling a higher likelihood of task switches were followed by smaller task switch costs.…”
Section: Cognitive Flexibility Can Be Triggered By Contextual Cuesmentioning
confidence: 99%